A Cross-Sectional Study of Urinary Neutrophil Gelatinase-Associated Lipocalin and its Association with Steroid Responsiveness in Iraqi Children with Idiopathic Nephrotic Syndrome - Abd Al Ridha, Ali M.; Kadhim, Dheyaa J.; Ali Alkhazrajy, Ayad H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Steroid-resistant nephrotic syndrome (SRNS)is associated with serious complications and financial burdens. Studies reported increased urinary neutrophil gelatinase-associated lipocalin (uNGAL) levels in children with idiopathic nephrotic syndrome (INS).Objectives: This study aimed to evaluate the uNGAL potential to distinguish SRNS from steroid-sensitive nephrotic syndrome (SSNS) in Iraqi children.Patients and Methods: Children with SRNS (n=31) and SSNS (n=32) were recruited from Babylon Hospital for Maternity and Pediatrics from March to June 2022. Patients' data included demographics, clinical characteristics, and urinary lab tests. The uNGAL concentrations were measured via a commercially available ELISA kit.Results: A significantly higher uNGAL median (p-value